2005
DOI: 10.1055/s-2005-870928
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Vascular Decompression versus Microvascular Decompression of the Trigeminal Nerve

Abstract: Microvascular decompression (MVD) is a highly accepted and effective method for treatment of patients with trigeminal neuralgia in whom compression of the nerve by a vascular structure is implicated in the pathogenesis of the disease. However, recent reports have highlighted the advantages of the endoscope in visualizing structures within the cerebellopontine angle. Additional research, using the endoscope to supplement the microscopic procedure, has demonstrated improved localization of neurovascular conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 11 publications
0
48
0
2
Order By: Relevance
“…2,7,11,21,24 All report excellent safety and short-to medium-term functional results. The largest of these, by Kabil et al, reported results for 255 patients with a favorable 3-year success rate and a lower rate of complications when compared with published series of microscopic MVD.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,11,21,24 All report excellent safety and short-to medium-term functional results. The largest of these, by Kabil et al, reported results for 255 patients with a favorable 3-year success rate and a lower rate of complications when compared with published series of microscopic MVD.…”
Section: Discussionmentioning
confidence: 99%
“…Although its use has been described as an adjunctive imaging modality in many surgical procedures the use of endoscopy as the sole means of intra-operative imaging in this setting has not been reported at that time. Microvascular decompressions were the first fully endoscopic procedures reported (Eby et al 2001, Jarrahy et al 2002a, Jarrahy et al 2002b, Kabil et al 2005, Cheng et al 2008). The first report of fully endoscopic resection of vestibular schwannoma was by Shainian and coworkers in 2004 (Shahinian et al 2004).…”
Section: Historical Perspective Of Endoscopic Surgery Of the Cerebellmentioning
confidence: 99%
“…Therefore, it has been generally accepted that MVD of the compressing vessels from the REZ is an effective treatment option for HFS 3,[12][13][14][15][16][17]19,22,23,26,29,33,39) . The REZ has been regarded as the area in which the sheath of the facial nerve is converted to the peripheral myelin composed of Schwann cells from the central glial myelin 6,13,35) .…”
Section: Compression Sitesmentioning
confidence: 99%